2013
DOI: 10.1038/ijir.2013.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessing satisfaction in men and their female partners after treatment with phosphodiesterase type 5 inhibitors for erectile dysfunction

Abstract: The Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS) and its partner version questionnaire were used to assess couples' satisfaction with the use of phosphodiesterase type 5 (PDE5) inhibitors to treat erectile dysfunction (ED) over a 3-month period. Of 161 ED patients, who together with their female partners were invited to answer separate questionnaires at home, 111 patients (68.9%; mean age 61.8 (23-87) years) and female partners (mean age 52.8 (22-77) years) returned completed questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
1
8
0
Order By: Relevance
“…The main reasons for the dissatisfaction were ineffectiveness of the medications. A recent study that assessed patients’ satisfaction using a questionnaire had showed a high satisfaction rate (95.5%) in users of PDE-5 inhibitors 55. In our study, the percentage of dissatisfaction might have been overestimated as therapeutic dissatisfaction of patients was judged on patients’ feedback that was recorded on the medical notes without any rating.…”
Section: Discussionmentioning
confidence: 60%
“…The main reasons for the dissatisfaction were ineffectiveness of the medications. A recent study that assessed patients’ satisfaction using a questionnaire had showed a high satisfaction rate (95.5%) in users of PDE-5 inhibitors 55. In our study, the percentage of dissatisfaction might have been overestimated as therapeutic dissatisfaction of patients was judged on patients’ feedback that was recorded on the medical notes without any rating.…”
Section: Discussionmentioning
confidence: 60%
“…The mean of initial prescription was 1.5 ± 0.7 packs (3 tablets/pack), and the refill rate of dapoxetine at 2nd visit was 73.9% (105/142). A total of 712 packs of dapoxetine were purchased during this study, with an average of 2.5 ± 2.5 packs per person. The mean follow‐up duration was 2.3 ± 2.1 months (0–9).…”
Section: Resultsmentioning
confidence: 99%
“…The diagnosis and classification of PE followed the guidelines of the ISSM (1). Based on the SHIM score, the severity of ED was classified as: severe ED (1-7), moderate ED (8)(9)(10)(11), mild-to-moderate ED (12)(13)(14)(15)(16), mild ED (17)(18)(19)(20)(21), and no ED (22)(23)(24)(25).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rational selection of an appropriate treatment is therefore dependent on an understanding of person-centered factors such as sexual behavior, yet relatively little is known about the preferences of men with ED regarding the degree of spontaneity or, conversely, planning of sexual intercourse 3, 4. Considerably more is known about treatment satisfaction of men receiving ED medications, although knowledge of treatment satisfaction within the context of understanding men’s sexual behavior may contribute to better meeting their needs 5, 6, 7…”
Section: Introductionmentioning
confidence: 99%